2013
DOI: 10.1111/acps.12217
|View full text |Cite
|
Sign up to set email alerts
|

Childhood maltreatment and inflammatory markers: a systematic review

Abstract: Childhood maltreatment is associated with a chronic inflammatory state independent of clinical comorbidities. However, studies are heterogeneous regarding CM assessment and definition. Important methodological improvements are needed to better understand the potential impact of CM on inflammatory response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
239
3
6

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 361 publications
(282 citation statements)
references
References 73 publications
25
239
3
6
Order By: Relevance
“…The association was not explained by key potential confounders, such as low birth weight, disadvantaged socio-economic conditions of the family, and low IQ, or by potential mediators, such as adult stressors, poor adult health, unhealthy behaviors, or acute infections at the time of inflammation assessment. Two dozen independent studies have since tested this association, and qualitative and quantitative reviews found reliable evidence of small elevations in inflammation biomarkers in maltreated individuals (Baumeister et al, 2015;Coelho et al, 2014). Of note, elevated inflammation levels are observed not only after maltreatment by adults, but also after other common and severe childhood stressors, such as bullying by peers (Takizawa et al, 2015).…”
Section: Brain Developmentmentioning
confidence: 98%
“…The association was not explained by key potential confounders, such as low birth weight, disadvantaged socio-economic conditions of the family, and low IQ, or by potential mediators, such as adult stressors, poor adult health, unhealthy behaviors, or acute infections at the time of inflammation assessment. Two dozen independent studies have since tested this association, and qualitative and quantitative reviews found reliable evidence of small elevations in inflammation biomarkers in maltreated individuals (Baumeister et al, 2015;Coelho et al, 2014). Of note, elevated inflammation levels are observed not only after maltreatment by adults, but also after other common and severe childhood stressors, such as bullying by peers (Takizawa et al, 2015).…”
Section: Brain Developmentmentioning
confidence: 98%
“…Maladaptive habits, including unhealthy diet and smoking, as well as environmental factors, including childhood abuse, have been consistently associated with pro-inflammatory activation 59 . For instance, individuals with a history of childhood abuse exhibit higher plasma CRP, IL-6 and TNF-α levels during adulthood in comparison to healthy controls 60 and are exposed to greater risk of chronic diseases in adulthood including cancer, depression, cardiovascular disease and metabolic syndrome 61 .…”
Section: Inflammatory Aberrations Associated With Depressionmentioning
confidence: 99%
“…In terms of mechanisms, it is noteworthy that early-life psychosocial stressors, notably emotional and sexual abuses are associated to early AAO [8,9]. Such stressful events are also known to induce acute and chronic immune/inflammatory alterations [10][11][12][13] possibly leading to an increased vulnerability to diabetes, obesity, cardiovascular disorders, autoimmunity, cancer and neurodegeneration commonly observed in adults with history of childhood maltreatment [14][15][16][17][18]. Of interest is that elevated C-reactive-protein (CRP), as well as high prevalence of cardiovascular disorders, type 2 diabetes mellitus, hypertension and obesity, are observed in early onset BD [19,20] and that some of these conditions even precede the diagnosis of BD in pediatric patients [20].…”
Section: Introductionmentioning
confidence: 99%